Spatial Colocalization of Human Ohnolog Pairs Acts to Maintain Dosage-Balance - Mc Lysaght, Aoife (My University, 2016)
Ohnologs-paralogous gene pairs generated by whole genome duplication-are enriched for dosage sensitive genes, that is, genes that have a phenotype due to copy number changes. Dosage sensitive genes frequently occur in the same metabolic pathway and in physically interacting proteins. Accumulating evidence reveals that functionally related genes tend to co-localize in the three-dimensional (3D) arrangement of chromosomes. We query whether the spatial distribution of ohnologs has implications for their dosage balance. We analyzed the colocalization frequency of ohnologs based on chromatin interaction datasets of seven human cell lines and found that ohnolog pairs exhibit higher spatial proximity in 3D nuclear organization than other paralog pairs and than randomly chosen ohnologs in the genome. We also found that colocalized ohnologs are more resistant to copy number variations and more likely to be disease-associated genes, which indicates a stronger dosage balance in ohnologs with high spatial proximity. This phenomenon is further supported by the stronger similarity of gene co-expression and of gene ontology terms of colocalized ohnologs. In addition, for a large fraction of ohnologs, the spatial colocalization is conserved in mouse cells, suggestive of functional constraint on their 3D positioning in the nucleus.
PUBLISHED
Keywords: colocalized ohnologs; Ohnologs-paralogous gene pairs; Dosage sensitive genes; Ohnologs; Dosage balance; Spatial colocalization; Copy number variation; Disease-associated genes